বিশ্বসাহিত্য কেন্দ্র ও আমি - সায়ীদ, আব্দুল্লাহ আবু
Articles chiefly on Bishwasahitya Kendra, a literary forum of international scope, located at Dhaka, Bangladesh; includes interviews with its founder, the author.